HUBUNGAN EKSPRESI EPIDERMAL GROWTH FACTOR RECEPTOR (EGFR) TERHADAP STADIUM KLINIS KARSINOMA SEL SKUAMOSA KULIT - Pramesti, Tisya Amanah (JURNAL IBNU SINA BIOMEDIKA, 2019)
Introduction:  EGFR is a molecule that plays a role in controlling cell growth especially the process of cell proliferation, angiogenesis, and inhibition of apoptosis. The high expression of EGFR found in a tumor tissue indicates the level of progression of the tumor which is symbolized by the clinical stage. Aims: This study aimed to determine the relationship of EGFR expression to the clinical stage of skin squamous cell carcinoma. Method: This study used a cross-sectional study which was an analytic observational study and correlation analysis of relationships between variables. A total of 20 paraffin block samples were diagnosed with both keratin and non-keratin skin squamous cell carcinoma were staining by immunohistochemical EGFR. The staining results are given a value with a scoring system using a light microscope. Results: Relation of EGFR expression to clinical stage Skin squamous cell carcinoma was assessed using the Rank Spearman correlation test. From 20 samples found 8 samples (40%) showed the expression with the highest scoring that is positive 3. The test results showed a significant relationship between EGFR expression on the clinical stage of skin Squamous Cell Carcinoma indicated by p value  0.001 (<0.05) and a very strong relationship as indicated by the relation coefficient value 0.857 (0.76-0.99). Conclusion: There is a very strong relationship between EGFR expression on the clinical stage of skin squamous cell carcinoma.  Keywords: Squamous Cell Carcinoma, expression, EGFR, clinical stage.